Bacteriologic Coprology - Libedinsky, Simón (Universidad Nacional de Córdoba, 1927)
When, in November 1926, I published in the "Revista del Centro Estudiantes de F. y Bioquímica" my Marcha sistemática, I did so respecting in every detail the wording and content of the paper that, with the same title, I presented at the Fourth Conference on Hygiene and Microbiology (B. Aires, July 1926). In this work, which I am now publishing, I have only expanded on that one, which in its fundamental part has not changed. The differential characters indicated, and the general course of the analysis, are the same. I have only added some notes and added, to the set of morphologically identical microbial species (and to which my previous work was circumscribed) other microorganisms that can be found in the course of a stool culture.